Characterization of polymer-liquid crystal blends - Filip Daniela; Simionescu Cristofor I.; Macocinschi Doina (Journal of the Serbian Chemical Society, 2001)
Blends of semi-crystalline polymers (polyethylene adipate and two poly(ester-urethane) s) with liquid crystal cholesteryl palmitate with different compositions were prepared by solution casting. One of the poly(ester-urethane)s was based on 2,4-tolylene diisocyanate (TDI) and the other one on 4,4’-diphenylmethane diisocyanate (MDI). The miscibility and phase transition were investigated over the whole range of concentration by differential scanning calorimetry and polarizing optical microscopy.